The gift : 12 lessons to save your life - Eger, Edith Eva; Weigand, Esmé Schwall (Scribner, 2020)
The author draws on her experiences as a Holocaust survivor, as well as the lives of her patients, to offer practical, uplifting advice about how to recognize and stop destructive, self-sabotaging patterns to find freedom and greater life fulfillment.